2010
DOI: 10.1097/meg.0b013e32833bec1e
|View full text |Cite
|
Sign up to set email alerts
|

The H63D genetic variant of the HFE gene is independently associated with the virological response to interferon and ribavirin therapy in chronic hepatitis C

Abstract: Of the 264 patients, 88 (32.1%) had SVR whereas 67.9% had nonresponse or relapse. Liver iron deposits were observed in 49.2% of the patients. The factors associated with SVR were hepatitis C virus genotype 2 or 3, transferrin saturation value of 45% or less, and detection of the H63D mutation. HFE mutation was more frequent in patients with iron deposits, but without association with serum iron biochemistry or severity of liver disease. Steatosis was more frequent in patients with liver iron deposits. CONCLUSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 63 publications
0
8
0
1
Order By: Relevance
“…Further, subgroup analyses showed that the best outcomes were achieved in studies in which patients were either predominantly HIV-negative (HIV−), predominantly infected with an HCV genotype other than 1 or 4, or treated with ribavirin. The proportion of patients who achieved an SVR in the 20 studies that included patients with all three of these characteristics ranged from 45% (95% CI: 34-55) 70 to 78% (95% CI: 61-91) 71 and the pooled proportion was 65% (95% CI: [61][62][63][64][65][66][67][68]. The presence of the interleukin-28B polymorphism was associated with a high SVR rate in the two studies which reported relevant data.…”
Section: Study Outcomesmentioning
confidence: 94%
“…Further, subgroup analyses showed that the best outcomes were achieved in studies in which patients were either predominantly HIV-negative (HIV−), predominantly infected with an HCV genotype other than 1 or 4, or treated with ribavirin. The proportion of patients who achieved an SVR in the 20 studies that included patients with all three of these characteristics ranged from 45% (95% CI: 34-55) 70 to 78% (95% CI: 61-91) 71 and the pooled proportion was 65% (95% CI: [61][62][63][64][65][66][67][68]. The presence of the interleukin-28B polymorphism was associated with a high SVR rate in the two studies which reported relevant data.…”
Section: Study Outcomesmentioning
confidence: 94%
“…Seven related studies that fulfilled the inclusion and exclusion criteria were included in the meta-analysis (Distante et al 2002;Cardoso et al 2004;Lebray et al 2004;Bonkovsky et al 2006;Yu et al 2006;Carneiro et al 2010;Sikorska et al 2010). The characteristics of each are summarized in Table 1.…”
Section: Meta-analysis Of Hfe Mutations and Svr Ratementioning
confidence: 99%
“…Various forms of interferon-based antiviral therapy have been developed and are in widespread use worldwide. Despite the growing body of evidence, however, no consensus describing the precise SVR-related role or mechanism of these mutations has been reached (Distante et al 2002;Cardoso et al 2004;Lebray et al 2004;Bonkovsky et al 2006;Yu et al 2006;Carneiro et al 2010;Sikorska et al 2010). Thus, we performed a metaanalysis of the related studies published to date in the peerreviewed literature to determine whether HFE mutations play a significant role in the SVR of chronic HCV infection treated with interferon-based therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated serum ferritin has long been recognized as a marker of poor response to antiviral treatment in chronic HCV infected patients (3,12,16) , however the mechanism underlying this effect is not clear and the role of HFE polymorphisms has not yet been established. Interestingly, there is intriguing evidence of an association between HFE polymorphism and higher SVR rates (8,31) , but this issue has not been specifically investigated among HCV patients with high serum ferritin, which are recognized as having difficult to treat disease.…”
Section: Introductionmentioning
confidence: 99%